Zonificación y caracterización geotécnica de los suelos de la sede central del Instituto Tecnológico de Costa Rica - Masís-Flores, Daniel Emilio (Instituto Tecnológico de Costa Rica, 2017)
The present investigation comprises a progressive development of different stages that begin with the compilation and analysis of geotechnical studies of the buildings of the headquarters of Technoligical of Costa Rica. Information has been obtained through field and laboratory test, such as the Standard Penetration Test (SPT), granulometry, Atterberg Limits and moisture content, provide the necessary data for the classification and quantification of soil bearing capacity. As a final step and objective of the Project, statistically validated maps of the classification and permisible soil capacity are generated at different depths, by means of the spatial interpolation of Ordinary Kriging and the Weighted of the Inverse Distance (IDW) method, The probes are properly georeferenced by Global Navigation Satellite System (GNSS), and ArcGis 10.3 software. At the end of the work the profiles of each perforation are presented and as aid to explain the reliability of the maps are included maps of prediction of error, tables and graphs with geostatistical information; It is concluded that for the choice of an appropriate spatila interpolation method, special attention should be paid to the distribution of data in the simple space and generated error.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2017.
Keywords: Kriging; IDW; Geoestadística; Interpolación espacial